The Influence of Audit Costs, Audit Engagement and Audit Rotation on Audit Quality - Nurul Fauziyah; Novi Darmayanti (Master of Accounting Universitas Trunojoyo Madura, 2021)
This study aims to determine the relationship between audit costs, audit engagement, audit rotation on audit quality in textile and garment manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The research method used a quantitative approach, while the data source used was secondary data. The study population was 16 companies in the textile and garment subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. The sampling method is purposive sampling method, namely the technique of determining the sample with certain considerations. The method of analysis uses multiple linear regression analysis. Partially, it shows that audit costs have a significant effect on audit quality, while engagement auditing has no effect on audit quality, and audit rotation has no significant effect on audit quality. Simultaneously, audit cost, audit engagement and audit rotation have a significant effect on audit quality.